Characteristics of cadmium immobilization in the cell wall of root in a cadmium-safe rice line (Oryza sativa L.). (February 2020) - Yu, Haiying; Guo, Jingyi; Li, Qin; Zhang, Xizhou; Huang, Huagang; Huang, Fu; Yang, Anqi; Li, Tingxuan
Abstract: Cultivating cadmium (Cd)-safe rice lines, which show low Cd accumulation in brown rice, is generally beneficial to ensure food safety. The Cd retention in root of Cd-safe rice line D62B plays an important role in its low Cd translocation from root to shoot. To understand the mechanism of Cd retention in root, a hydroponic experiment was conducted to investigate the subcellular distribution of Cd and the contribution of polysaccharides to Cd binding to the root cell wall of a Cd-safe rice line D62B with a common rice line Luhui17 as a control material. D62B retained more Cd in the root by sequestrated a higher proportion of Cd in the cell wall, further it transferred less Cd to shoot. Close to half of the Cd in the root cell wall of D62B was accumulated in the hemicellulose 1 (HC1), and the proportions of HC1 in it were 1.2–1.7 times higher than these of Luhui17. The proportion of Cd in the pectin showed a dose-dependent increase in two rice lines. D62B contained significantly higher uronic acid concentrations of the pectin and greater pectin methyl esterase (PME) activities than Luhui17 in the root cell wall. These results indicated that a superior Cd binding capacity of the cell wall polysaccharides in D62B played an important role in its Cd retention in root. Highlights: D62B contained more Cd in cell wall, further affected Cd retention in roots than Luhui17. The Cd was mainly immobilized in pectin and hemicellulose 1 of cell wall in roots. D62B showed higher uronic acid concentration in root cell wall especially pectin than Luhui17. The pectin methylesterase activity in root cell wall of D62B was stronger than that of Luhui17.